1997
DOI: 10.1017/s0140525x97221485
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in pain

Abstract: Are there sex differences in pain? For experimentally delivered somatic stimuli, females have lower thresholds, greater ability to discriminate, higher pain ratings, and less tolerance of noxious stimuli than males. These differences, however, are small, exist only for certain forms of stimulation and are affected by many situational variables such as presence of disease, experimental setting, and even nutritive status. For endogenous pains, women report more multiple pains in more body regions than men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
504
3
33

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 968 publications
(578 citation statements)
references
References 0 publications
38
504
3
33
Order By: Relevance
“…23 For experimentally delivered somatic stimuli, females have lower thresholds, greater ability to discriminate, higher pain ratings and less tolerance of noxious stimuli than males. The gender difference found in the present study was therefore not unexpected, even though there are, to our knowledge, no previous reports on gender differences in the prevalence of neuropathic pain.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…23 For experimentally delivered somatic stimuli, females have lower thresholds, greater ability to discriminate, higher pain ratings and less tolerance of noxious stimuli than males. The gender difference found in the present study was therefore not unexpected, even though there are, to our knowledge, no previous reports on gender differences in the prevalence of neuropathic pain.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…For example, some chronic diseases, including migraine, temporomandibular disorders, fibromyalgia, arthritis, and interstitial cystitis, are more prevalent in females [1,2]. Women usually display stronger pain perception and request more analgesics [3,4], while in pregnancy, increasing estrogen and progestogen have an anti-nociceptive role [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study has investigated the use of pain descriptors when classifying SCI pain and concluded that verbal descriptors alone are not su cient for pain classi®cation. 25 In non-SCI populations, women often report more numerous pain locations than men 17,19 and more severe pain. 18 This was not the case in our study, where no di erences were found.…”
Section: Discussionmentioning
confidence: 99%